2020
DOI: 10.1002/jhbp.793
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological features of immunoglobulin G4‐related sclerosing cholangitis in Japan

Abstract: Background/Purpose Epidemiological data on immunoglobulin G4‐related sclerosing cholangitis (IgG4‐SC) are scarce. Method We randomly selected healthcare facilities from a list of all facilities in Japan. The selection rate was determined according to a stratification based on the facility characteristics and scale. We sent questionnaires to the selected facilities enquiring about the number and sex of patients with IgG4‐SC in 2018. Among responding facilities, we further inquired about the clinical characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 26 publications
2
26
0
Order By: Relevance
“…On the other hand, approximately 10% of patients with IgG4-SC are not diagnosed with AIP; therefore, the estimated prevalence of IgG4-SC could theoretically be as high as 2.0 cases per 100,000 inhabitants. Finally, in 2020, Tanaka et al published the first epidemiological study evaluating 1,045 IgG4-SC patients from 532 centers in Japan and showed that the prevalence of IgG4-SC in 2018 was 2.18 (95% confidence interval, 2.13–2.23) per 100,000 inhabitants, which is comparable to other data [ 20 ]. Thus, we can conclude that the prevalence of IgG4-SC in Japan is higher than the prevalence of PSC, which in 2016 was 1.80 (95% CI, 1.75–1.85) [ 21 ].…”
Section: Epidemiologysupporting
confidence: 56%
“…On the other hand, approximately 10% of patients with IgG4-SC are not diagnosed with AIP; therefore, the estimated prevalence of IgG4-SC could theoretically be as high as 2.0 cases per 100,000 inhabitants. Finally, in 2020, Tanaka et al published the first epidemiological study evaluating 1,045 IgG4-SC patients from 532 centers in Japan and showed that the prevalence of IgG4-SC in 2018 was 2.18 (95% confidence interval, 2.13–2.23) per 100,000 inhabitants, which is comparable to other data [ 20 ]. Thus, we can conclude that the prevalence of IgG4-SC in Japan is higher than the prevalence of PSC, which in 2016 was 1.80 (95% CI, 1.75–1.85) [ 21 ].…”
Section: Epidemiologysupporting
confidence: 56%
“…IgG4-related disease most commonly affects males with a male to female ratio around 3:1 and the mean age ranges around 60 years [4]. IgG4 sclerosing sialadenitis and dacryoadenitis is a rare condition that is also known as Mikulicz's disease.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of IgG4-RD is yet to be fully understood. However, it is considered to be relatively favorable with a 10-year overall survival rate of 89.0% [4]. The majority of the patients respond well to corticosteroids; however, the risk of recurrence is common after discontinuation of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…IgG4-SC is a distinct form of chronic cholangitis characterized by infiltration of lymphocytes and abundant IgG4-positive plasma cells in the bile duct wall, elevated IgG4 serum levels in the majority, and strong response to corticosteroid therapy [ 85 ]. From the epidemiological point of view, a recent epidemiological survey conducted in 1180 departments from health centres across Japan on the basis of a questionnaire, estimated a 2.18 prevalence of IgG4-SC per 100,000 population [ 86 ]. This condition can be divided into two types: the major type is IgG4-SC associated with AIP, whereas the minor type is isolated IgG4-SC [ 85 ].…”
Section: Introductionmentioning
confidence: 99%
“…This condition can be divided into two types: the major type is IgG4-SC associated with AIP, whereas the minor type is isolated IgG4-SC [ 85 ]. Patients with IgG4-SC and with associated AIP are generally older (mean age 62 years), men (85%) presenting with obstructive jaundice [ 86 ]. Indeed, IgG4-SC produces stenosis in the lower bile duct, and thus should be differentiated from pancreatic cancer and cholangiocarcinoma.…”
Section: Introductionmentioning
confidence: 99%